Kontribusi Usaha Perempuan dalam UMKM Berbasis Potensi Lokal terhadap Perekonomian Keluarga di Kabupaten Purworejo (Progress, 2025)
Abstract. This study aims to analyze the role of women-led enterprises in strengthening family economies through MSMEs based on local natural resource utilization in Purworejo Regency in 2025. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving women MSME actors who utilize local commodities such as coconut, cassava, chili, and livestock products. Informants were selected purposively based on their active involvement in business and contribution to household income. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings reveal that women’s enterprises contribute significantly to household income, fulfillment of family needs, and family economic resilience. Women’s motivations extend beyond economic necessity to include independence, self-confidence, and self-actualization. The utilization of local natural resources creates product value-added that supports business sustainability. This study highlights women’s roles as family economic agents and drivers of local resource-based economic development. Theoretically, the findings reinforce household economic theory and women empowerment perspectives. Practically, the results imply the importance of training support, microfinance access, and marketing strengthening for women-led MSMEs. Keywords: women’s enterprises, MSMEs, family economy, women empowerment, local natural resources